2009
DOI: 10.1523/jneurosci.2477-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Directional Selectivity for Frequency-Modulated Sweeps in the Inferior Colliculus Revealed byIn VivoWhole-Cell Recordings

Abstract: Auditory neurons in the inferior colliculus (IC) show remarkable selectively in that they can distinguish between complex sounds that have identical spectral energy but different temporal structure, such as frequency modulations (FMs) that sweep either upward or downward. Extracellular recordings show that blocking inhibition locally reduces or eliminates response selectivity, suggesting that selectivity is created de novo in the IC, with inhibition playing a prominent role. However, these studies can only inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
107
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(113 citation statements)
references
References 56 publications
(101 reference statements)
6
107
0
Order By: Relevance
“…Whole-cell patch recordings from visual cortical neurons showed, contrary to conclusions reached from pharmacologically blocking inhibition (34), that orientation selectivity can result from integration of excitatory thalamic inputs (35). Recent intracellular (particularly whole-cell) recordings have shown that biologically relevant stimuli can elicit diverse and complex patterns of excitation and inhibition in midbrain neurons (3,19,20,23,(36)(37)(38)(39)(40), suggesting that inhibition plays important computational roles. Our results provide direct evidence that GABA A antagonists can attenuate stimulusdriven inhibition and markedly reduce short-pass duration selectivity; bicuculline and the more selective GABA A antagonist, gabazine, had similar effects.…”
Section: Discussionmentioning
confidence: 97%
“…Whole-cell patch recordings from visual cortical neurons showed, contrary to conclusions reached from pharmacologically blocking inhibition (34), that orientation selectivity can result from integration of excitatory thalamic inputs (35). Recent intracellular (particularly whole-cell) recordings have shown that biologically relevant stimuli can elicit diverse and complex patterns of excitation and inhibition in midbrain neurons (3,19,20,23,(36)(37)(38)(39)(40), suggesting that inhibition plays important computational roles. Our results provide direct evidence that GABA A antagonists can attenuate stimulusdriven inhibition and markedly reduce short-pass duration selectivity; bicuculline and the more selective GABA A antagonist, gabazine, had similar effects.…”
Section: Discussionmentioning
confidence: 97%
“…Nothing is known of sweep selectivity at lower levels of the pallid bat auditory system, but in other species, direction and/or rate selectivity has been reported in the cochlear nucleus (Britt and Starr 1976;Godfrey et al 1975) and nuclei of the lateral lemniscus (Huffman et al 1998), as well as an extralemniscal region of the IC (Gordon and O'Neill 2000). The modeling of synaptic inputs to IC neurons further suggests that the inputs themselves may be selective for sweep direction and rate (Gittelman et al 2009). Grothe 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Convergence of excitation and inhibition produces a host of response profiles in the central auditory system, including selectivity for stimulus frequency (Fuzessery and Hall, 1996;Wehr and Zador, 2003;Wu et al, 2008;Xie et al, 2008;Fukui et al, 2010), intensity , spatial position/sound localization (Rose et al, 1966;Fuzessery and Pollak, 1985;Zhang and Kelly, 2010;Tang et al, 2011), amplitude modulation (Grothe, 1994;Burger and Pollak, 1998), rhythm detection (Felix et al, 2011), FM sweep direction (Gittelman et al, 2009;Gittelman and Pollak, 2011), and pulse-echo delay (Galazyuk et al, 2005;Yavuzoglu et al, 2011). Inhibition shapes and sharpens neural responses by modulating the latency, strength, and time course of excitation.…”
Section: Duration Tuning and Other Auditory Feature Detectorsmentioning
confidence: 99%
“…Upward and downward FM sweeps evoke suprathreshold EPSPs of different magnitudes in IC neurons; however, IPSPs raise the spiking threshold of the cell to just below the largest excitatory input magnitude. This selects for only the strongest excitatory input and thus the corresponding FM sweep direction (Gittelman et al, 2009). Inhibitory inputs to DTNs are responsible for decreasing spike counts and sharpening temporal response profiles by increasing the spiking threshold of a neuron (Fig.…”
Section: Duration Tuning and Other Auditory Feature Detectorsmentioning
confidence: 99%